(untitled) (Research, Society and Development, 2024)
Objective: To propose a ventilation correction for the various causes of reverse triggering (RD). Method: this is an observational study, with a descriptive objective and a qualitative approach, where patients undergoing invasive mechanical ventilation (IMV) were analyzed, with a sample size of 19 individuals, fully sedated and/or blocked, presenting reverse firing asynchrony. The expiratory pause maneuver of approximately 3 seconds was used to classify the groups of patients with reflex reverse triggering (DRR) Vs low drive (DRB). In the absence of muscle pressure (Pmus), these were classified in the DRR group and those who showed Pmus activation in the DRB group. Results: It was observed that correction maneuvers aimed at reducing lung strain, such as reducing total tidal volume (VT), reducing programmed respiratory frequency (RR) and reducing positive end-expiratory pressure (PEEP) were effective. for the correction of the DRR group. Ventilatory adjustment procedures with determination of support RR (10 to 12ipm), associated with reduction or stop of sedation/blocker, were efficient for patients in the DBB group. Conclusion: it is noted that the determination and classification of the different causes of DR can guide clinical correction procedures in addition to appropriate ventilation adjustments for each group of these asynchronies, the DRR and DRB. It is noted that the determination and classification of the different causes of DR can guide clinical correction procedures in addition to appropriate ventilation adjustments for each group of these asynchronies, those of RRD and DRB. Cases of RRD (involuntary-reflex DR) showed a 50% success rate in the given therapy, with greater research needs to identify with greater accuracy the etiology of the reflex cause, so that new correction methods are available in the scientific field, to the correction of this reflex dyssynchrony.